2014
DOI: 10.1590/0100-2945-424/13
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de porta-enxertos de pessegueiro obtidos de miniestacas, em duas épocas, e sistema de cultivo sem solo

Abstract: A propagação vegetativa comercial de mudas de pessegueiro por estaquia no Brasil tem sido limitada por alguns fatores, como a falta de técnicas apropriadas de manejo do ambiente de propagação, além da dificuldade no manejo da nutrição e da sobrevivência das estacas pós-enraizamento. Objetivou-se com o presente estudo avaliar o crescimento e sobrevivência de porta-enxertos de pessegueiro clonados através da miniestaquia, em sistema de cultivo sem solo, obtidos em duas épocas. Conduziu-se o trabalho em casa de v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
14
0
2
Order By: Relevance
“…This technique aims to reduce the vigor of plants, increase yield efficiency, and improve fruit quality. These effects have already been verified in several fruit species, such as peach (Rufato et al, 2006;Scarpare Filho et al, 2000;Telles, Biasi, Mindello Neto, & Peters, 2006;Tomaz, Schuch, Peil, & Timm, 2014), orange (Guilherme, Marinho, Biazatt, Campos, & Bremenkamp, 2014), pear (Baciu, Achim, & Cosmulescu, 2008), apple (Marcon Filho, Rufato, Rufato, Kretzschmar, & Zancan, 2009;Vaio, Cirillo, Buccheri, & Limongelli, 2009), cherry (Magyar & Hrotkó, 2008), and mango (Posada & Guzmán, 2009). Theoretically, rootstocks may indirectly affect fruit quality by several mechanisms, including budburst, time and abundance of scion flowering and flower quality (Daza, Galavis, Grande, & Santamaria, 2008).…”
Section: Introductionmentioning
confidence: 79%
“…This technique aims to reduce the vigor of plants, increase yield efficiency, and improve fruit quality. These effects have already been verified in several fruit species, such as peach (Rufato et al, 2006;Scarpare Filho et al, 2000;Telles, Biasi, Mindello Neto, & Peters, 2006;Tomaz, Schuch, Peil, & Timm, 2014), orange (Guilherme, Marinho, Biazatt, Campos, & Bremenkamp, 2014), pear (Baciu, Achim, & Cosmulescu, 2008), apple (Marcon Filho, Rufato, Rufato, Kretzschmar, & Zancan, 2009;Vaio, Cirillo, Buccheri, & Limongelli, 2009), cherry (Magyar & Hrotkó, 2008), and mango (Posada & Guzmán, 2009). Theoretically, rootstocks may indirectly affect fruit quality by several mechanisms, including budburst, time and abundance of scion flowering and flower quality (Daza, Galavis, Grande, & Santamaria, 2008).…”
Section: Introductionmentioning
confidence: 79%
“…In this sense, the use of this method might be a suitable option for sites where the use of rootstocks does not present any clear advantage, such as nematode resistance (OLIVEIRA et al, 2003). A study of vegetative propagation of selfrooted Maciel plants through minicuttings in a semi-hydroponic system, concluded that this system improves the development of self-rooted peach seedlings (rooting > 90%) compared to propagation through minicuttings in plastic bags (TOMAZ, 2014). The cutting method combined with the semihydroponic system could, therefore, be an interesting alternative to seed propagation, because it provides better tree uniformity (excludes the possibility of genetic variability), reduces of the time needed for seedling production, and increases the possibility of producing well-nourished seedlings with strong root systems (TOMAZ, 2014).…”
Section: Self-rooting (Sr)mentioning
confidence: 99%
“…An investigation by Tomaz (2014), which involved semi-hardwood cutting propagation in a semi-hydroponic system using sand as the substrate, demonstrated the favorability of a soilless technique. The resultant plants in this study were found to have average lengths that were three times longer than those from an independent study that was conducted during the same time frame, which involved a conventional system (CS), (PICOLOTTO et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, peach production has presented significant growth (TOMAZ et al, 2016). According to FAO (2008) data, Brazil is the 13 th largest world's peach producer.…”
Section: Introductionmentioning
confidence: 99%